RANCANG BANGUN APLIKASI E-VOTE PEMILIHAN KETUA RT PADA PERUMAHAN DUTA ASRI PALEM 7 BERBASIS WEB - Firdiansyah Firdaus Basri; Anggrin Novri Yenti; Rohmat Taufik (University of Muhammadiyah Tangerang, 2021)
This web-based E-Voting was created to facilitate the election of the RT Chair at Duta Asri Palem 7 Housing. The problem currently being faced is that in the ongoing elections, many residents cannot attend, there are still multiple elections and the vote count is still manual. The purpose of making this e-voting is to make it easier for residents to choose the Chair of the RT anywhere so that the expected vote results are more leverage. The research methods used in making this e-voting are field studies, literature studies and interviews. And the design method used by the researcher is the SDLC (System Development Life Cycle) method which is the whole process of building a system through several steps such as Planning, Analysis, Design and Implementation. The e-voting application is built with the PHP programming language, and utilizes the MySQL database as a database server. The expected result of making e-voting is that the problems that have occurred so far can be minimized and can streamline time and improve performance in carrying out the election of RT Chair in Housing Ambassador Asri Palm 7.